Theory into research practice: reflections and recommendations on collaborative feminist research - Harvey, Rebecca G.; Brown, Kristina S.; Miller, Bobbi J.; Williams-Reade, Jacqueline; Tyndall, Lisa; Murphy, Megan J. (Journal of Feminist Family Therapy, 2016)
Six women faculty came together to research their peers asking other women in COAMFTE-accredited programs about their personal and professional identities. The goal of this research was to develop recommendations for the field of Couple/Marriage and Family Therapy to support the engagement and advancement of women faculty. The research collaboration itself became a heuristic, feminist praxis, a co-creation of insight, support network, and professional relationships which had liberating results for the collaborators. We intended to create a research project that would be collaborative, empowering, and transformative for participants; in the process, the collaboration became empowering and transformative for ourselves. This article will reflect on our experiences and provide recommendations for future feminist research teams. Copyright © Taylor & Francis Group, LLC.
Keywords: clinical article; collaboration; dept.mft; family therapy; female; feminism; feminist research; gender; human; insider/outsider; marriage; university

Using CBPR methods in college health research exploring excessive alcohol consumption - Bulmer, Sandra Minor; Barton, Barbara A; Liefeld, Julie; Montauti, Sara; Santos, Stephanie; Richard, Melissa; Hnath, Laura; Pelletier, Kara; Lalanne, Jude (Journal of Adolescent Research, 2016)
Community-based participatory research (CBPR) is a collaborative methodology that uniquely involves stakeholders in all stages of the research process. CBPR has been widely utilized in the field of public health, but not widely employed with college populations. This study utilized CBPR methods within a college community to gain insight into excessive alcohol consumption. Six student researchers planned and carried out a rigorous qualitative study at a public university in the Northeast region of the United States. A total of 48 undergraduate participants were recruited for focus groups that were facilitated by two student researchers, and transcribed and analyzed using thematic analysis methods. Students' reasons for drinking alcohol were focused within the themes of inclusion, habitual default, and the student development process. Social media, strict policy/enforcement, and student's desire to avoid responsibility led to increased risk and consequences related to drinking. Students recommended late night transportation and a Good Samaritan policy as strategies to improve student safety. This study led to student advocacy and policy change directed at improving student's health and safety and demonstrated that CBPR methods show promise for engaging students and producing meaningful data.
Keywords: college issues; dept.hhs; dept.mft; emerging adulthood; health; qualitative methods; substance use